PENGARUH SUPERVISORS DIFFICULT GOALS TERHADAP ABUSIVE SUPERVISION DENGAN HINDRANCE STRESS, ANGER, DAN ANXIETY SEBAGAI VARIABEL MEDIASI (Studi pada Pegawai Bank Mandiri Cabang Banda Aceh) - Fitria Dian Islami, Saiful Bahri (Departemen Manajemen, 2016)
This study aims to explore the impact of Supervisor Difficult goals on Abusive Supervision while considering Hindrance Stress, Anger, and Anxiety as a mediating variable. The sample for this research is consisted of 111 employess from banks Mandiri branch of Banda Aceh. This research used a questionnaire as the research instrument method. The probability sampling technique is used in this research. The technique of taking total sample population is simple random sampling. Hierarchical analysis methods Linear Modeling (HLM) was used as a method of analysis to determine the effect to the variables involved. SPSS 20 is used for analyzing the data. Correlation and regression analysis is used to test the direct and mediating relationship between key variable. Result indicate that both the first stage Difficult Goals effect on significant Anger and Anxiety. Difficult Goals effect on significant Hindrance stress. Hindrance stress effect on significant Anger and Anxiety. Difficult goals effect on significant Anger and Anxiety mediating the Hindrance Stress. The second stage, Hindrance stress effect on significant Abusive Supervision. Hindrance Stress effect on significant Anger and Anxiety. Anger and Anxiety effect on significant Abusive Supervision. Hindrance Stress effect on Abusive Supervision mediating the Anger and Anxiety from employee Bank Mandiri branch of Banda Aceh branch. Keywords: Difficult Goals, Hindrance Stress, Anger, Anxiety, Abusive Supervision.